Efficiency Loss of Mixed Equilibrium Behaviors with Polynomial Cost Functions - Yu, Xiaojun; Huang, Hai-Jun (Promet - Traffic&Transportation, 2012)
This paper investigates the efficiency loss of selfish routing simultaneously with user equilibrium (UE) player and Cournot-Nash (CN) players. The upper bound of the efficiency loss of UE-CN mixed equilibrium with polynomial cost functions is obtained by the scaling method and the nonlinear programming method, respectively. It is shown that the upper bound of efficiency loss obtained by the scaling method only depends on the polynomial degree of the link travel cost function and the upper bound of efficiency loss obtained by the nonlinear programming method depends on the number of the CN players besides the aforementioned factors. The numerical tests validate our analytical results.KEY WORDS: efficiency loss, UE-CN mixed equilibrium, variational inequality, selfish routing game